Складні слова в мові сучасної української преси: структура та стилістичні функції - Мислива-Бунько, Іванна Ярославівна; Myslyva-Bunko, Ivanna Ya. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Роботу присвячено комплексному теоретичному обґрунтуванню складних слів як інформаційному, лаконічному, мовновиражальному і стилістичному засобу. Проаналізовано теоретичні засади вивчення складних слів у лінгвістиці, принципи їхнього виникнення; подано узагальнене тлумачення терміна „складне слово”; виділено спільні та відмінні риси осново-, словоскладання, зрощення й абревіації; виокремлено й схарактеризовано основні чинники активізації складних слів у мові сучасної української преси. Із позиції традиційного вчення проаналізовано способи творення складних слів (за частинами мови); окреслено своєрідні риси осново-, словоскладання, зрощення, абревіації складних іменників, прикметників, дієслів, дієприкметників, прислівників; класифіковано складні слова за лексико-семантичними параметрами; виявлено науживаніші словотвірні типи. Простежено стилістичне навантаження композитів, юкстапозитів, абревіатур у текстах газет і журналів, з’ясовано функційне призначення складних слів у заголовках статей.

This thesis presents the results of research which has been carried out in connection with a complex theoretical investigation and description of compound words as informational, laconic, language expressive and stylistic means. The main theoretical background of the investigation and the origin of compound words have been analyzed; a summarized explanation of the term „compound word” has been suggested; both common and differing features of stem and word formation, concretion and abbreviation have been described; and the main reasons for the frequent usage of compound words in the modern Ukrainian press have been differentiated and characterized. From the standpoint of the traditional approaches, various patterns of word formation have been analyzed (in terms of the parts of speech); some particular features of stem and word formation, concretion and abbreviation of nouns, adjectives, verbs, participles and adverbs have been provided; compound words have been classified according to lexical and semantic parameters; and the most widely-used word formation patterns have been identified. The stylistic peculiarities of composites, juxtapositionals (a multi-stem word which is made by means of word combination of word forms), abbreviations in newspaper and magazine texts are identified. The functions of compound words in newspaper headlines have been defined.
Compound Words in Modern Ukrainian Language of the Press: Structure and Stylistic Devices
Keywords: мова преси; газета; публіцистика; основоскладання; словоскладання; зрощення; абревіація; складне слово; композит; юкстапозит; абревіатура; семантика; стилістичні функції; the press language; newspaper; publicism; stem formation; word formation; concretion; abbreviation; a compound word; composite; juxtapositional; abbreviated word; semantics; stylistic devices